Getting it right - Gelb, Alan (Thomson/Delmar Learning, 2004)
Getting it Right: Milady's Survival Guide for Cosmetology Students is a fun-to-read collection of practical, proven tips and hints to make the life of a cosmetology student easier and more productive. Hundreds of short tips are organized by category, making the information easy to find and fun to look through. Tips range from the physical to the abstract and are grouped by categories, such as On the Clinic Floor, Studying for the Exam, and Getting Organized. Compiled from the actual experiences of students, teachers, and professionals throughout the US, the tips are easy to digest and remember. They offer some not-so-obvious ways to make cosmetology school more manageable and preparing for licensure less threatening. The compact size of the book makes it easy to tuck into a handbag or jacket pocket for browsing whenever time permits